The improvement of the winter wheat cultivation technology in arid conditions of the Povolzhie - О. I. Goryanin; Е. V. Madyakin; B. Zh. Dzhangabaev; N. А. Yakovleva (Зерновое хозяйство России)
Winter wheat is currently the main grain field crop in the European part of Russia. However, to increase the cultivation efficiency, it is necessary to improve cultivation technology. The purpose of the work is to identify new promising varieties and improve the winter bread wheat cultivation technology for the arid conditions of the Povolzhie. In 2015–2019 there was conducted an agroecological testing for 17 winter wheat varieties, which were most widespread and had the prospects for their introduction in the Povolzhie. During 2011–2018 there were studied five cultivation technologies (options) of the winter wheat variety ‘Svetoch’ in the six crop rotation sequences. The study has established that when cultivating winter wheat in the blackearth (chernozem) steppe of the Povolzhie, the varieties ‘Marafon’, ‘Novoershovskaya’, ‘Zhemchuzhina Povolzhiya’, ‘Severodonetskaya yubileynaya’ and ‘Svetoch’ were the most promising varieties. Under favorable moisture conditions, it was most profitable to cultivated the varieties ‘Rostovchanka 7’, ‘Izyuminka’, ‘Marafon’, ‘Bazis’, ‘Severodonetskaya yubileynaya’, ‘Skipetr’. When cultivating winter wheat in ‘black’ fallow, it is more rational to use early fallow, which begins to be cultivated in the spring when the soil is physically matured. The early spring additional fertilizing with ammonium nitrate increases winter wheat productivity on 0.28 t/ha (9.3%). In order to obtain the maximum net income (11324.8 rubles/ha) and profitability (115.0%), it is most expedient to use the biological product ‘Bionex Kemi’ (3 l/ha) on commercial wheat crops.